2021
DOI: 10.1093/gbe/evab202
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Transfer of Microbial Toxin Genes to Gall Midge Genomes

Abstract: A growing body of evidence has underscored the role of horizontal gene transfer (HGT) in animal evolution. Previously, we discovered the horizontal transfer of the gene encoding the eukaryotic genotoxin cytolethal distending toxin B (cdtB) from the pea aphid Acyrthosiphon pisum secondary endosymbiont (APSE) phages to drosophilid and aphid nuclear genomes. Here, we report cdtB in the nuclear genome of the gall-forming ‘swede midge’ Contarinia nasturtii (Diptera: Cecidomyiidae) via HGT. We searched all available… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 89 publications
1
10
0
Order By: Relevance
“…Remarkably, the cdtB copies in the non-Scaptomyza drosophilids and aphids encode the same intron-exon splice junctions. This gene has also been found in the genomes of cecidomyiid gall midges and thrips (Verster et al 2021).…”
Section: A Tale Of Two Toxinsmentioning
confidence: 80%
“…Remarkably, the cdtB copies in the non-Scaptomyza drosophilids and aphids encode the same intron-exon splice junctions. This gene has also been found in the genomes of cecidomyiid gall midges and thrips (Verster et al 2021).…”
Section: A Tale Of Two Toxinsmentioning
confidence: 80%
“…In insects some examples of HGT acquired genes involved in defense include bacterial lysozymes acquired by pea aphid, Acyrthosiphon pisum (Nikoh et al 2010) and by Halyomorpha halys (Ioannidis et al 2014). Recently, the acquisition by HGT of five toxin genes in C. nasturtii species was reported, which plays a nontrivial new role in insect immune function against eukaryotic enemies (Verster et al 2021). In line with our model, the authors postulated that most likely donors are microbes that share the same environment with swede midge.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis supports gene transfer from bacteria to insects. It is suggested that toxin genes might confer a protective function in developing larvae and pupae against other insect predators such as wasps [ 280 ].…”
Section: Insights Into the Evolution Of Bacterial Protein Toxinsmentioning
confidence: 99%